Novel dual‐layer‐oriented strategy for fully automated vehicles' lane‐keeping system. Issue 13 (27th January 2021) - An, Quan; Cheng, Shuo; Li, Liang; Peng, Haonan
Abstract : A novel concept of a dual‐layer‐oriented control strategy for fully automated vehicles' lane‐keeping system is proposed which consists of an inner controller with a modified preview driver model and an outer cooperative copilot controller. With designed weighting function of displacement error based on a hyperbolic tangent and adjustable preview horizon according to road geometry, the inner controller is supposed to track the lane centreline precisely and efficiently through optimal control framework. The outer controller is specially designed for situations where the vehicle may run out of the lane and cause a collision. Only when the vehicle is at high risk of lane‐crossing, the outer controller is activated to guide the vehicle back to lane centreline by exerting proper steering command, which is calculated by solving a model predictive control‐based constrained optimisation problem with a designed quadratic cost function. Finally, simulation tests based on CarSim‐Matlab joint platform are carried out to verify the proposed strategy. Results demonstrate that the modified preview driver model is able to improve path following performance and the dual‐layer‐oriented control strategy with less computational burden can effectively prevent the vehicle from crossing lane boundaries.